2018
DOI: 10.12678/1089-313x.22.1.54
|View full text |Cite
|
Sign up to set email alerts
|

Between-Day Reliability of Pre-Participation Screening Components in Pre-Professional Ballet and Contemporary Dancers

Abstract: Critical appraisal of research investigating risk factors for musculoskeletal injury in dancers suggests high quality reliability studies are lacking. The purpose of this study was to determine between-day reliability of pre-participation screening (PPS) components in pre-professional ballet and contemporary dancers. Thirty-eight dancers (35 female, 3 male; median age; 18 years; range: 11 to 30 years) participated. Screening components (Athletic Coping Skills Inventory-28, body mass index, percent total body f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…Previous intra-and inter-rater reliability studies investigating the relative reliability of a musculoskeletal profiling test battery comprising identical or similar tests to those used in the present study, reported intraclass correlations ranging from 0.30 ["poor"] to 0.97 ["excellent"] [4,11,12,22,23,25,[38][39][40][41][42][43][44]. This wide variation in intra-and inter-rater intraclass correlation values between tests was also evident in the present study (0.04 ["poor"] to 0.95 ["excellent"]).…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Previous intra-and inter-rater reliability studies investigating the relative reliability of a musculoskeletal profiling test battery comprising identical or similar tests to those used in the present study, reported intraclass correlations ranging from 0.30 ["poor"] to 0.97 ["excellent"] [4,11,12,22,23,25,[38][39][40][41][42][43][44]. This wide variation in intra-and inter-rater intraclass correlation values between tests was also evident in the present study (0.04 ["poor"] to 0.95 ["excellent"]).…”
Section: Discussionmentioning
confidence: 66%
“…Previously reported intra-and inter-rater reliability studies of musculoskeletal profiling test batteries in young individuals have primarily investigated general, symptomatic, non-soccer or sub-elite groups, suggesting there is a paucity of research evidencing the reliability of musculoskeletal profiling test batteries among young elite soccer players [10][11][12][13][14]. Of the two studies that have evaluated the reliability of musculoskeletal profiling test batteries in elite youth soccer players, the intraclass correlations for the tests in the batteries ranged from 0.51 ("fair") to 0.98 ("excellent"), while the coefficient of variations ranged from 0.4 to 12.4% [4,15].…”
Section: Introductionmentioning
confidence: 99%
“…The ACSI-28 was used to evaluate sports coping skills [ 19 , 20 ] ( Table 4 ). The ACSI-28 is composed of seven subvariables, including coping with adversity, peaking under pressure, goal setting/mental preparation, concentration, freedom of worry, confidence and achievement motivation, and coachability, and consists of a total of 28 questions with four items for each subscale.…”
Section: Methodsmentioning
confidence: 99%
“…The image created by dance gives people a sense of "nobility and elegance." Strictly according to the aesthetic standards of the court, the aesthetic standards of dance were formulated, and the dance movements were sorted and named, which has been continued to this day, and thus laid the foundation for the [5,6]. Therefore, the terminology of ballet is basically composed of French [6].…”
Section: Multimedia Ballet Basic Skillsmentioning
confidence: 99%